CORE OUTPUTS OF THE PROJECT FLAVIA - ACTION PLANS FOR LOGISTICS CHAINS TO REMOVE BOTTLENECKS (Perner's Contacts, 2012)
This article belongs to publishing of the European project FLAVIA. This project is now in last, implementation phase where one of the core outputs are action plans for logistic chains. This article summarizes data and output for Czech Republic in the field of infrastructure, terminals and legislation.
Keywords: logistic chain, FLAVIA, action plan